A model of cyclical terrorist murder in Colombia, 1950-2004. Forecasts 2005-2019 - Gomez-Sorzano, Gustavo
Abstract: This paper continues a research born in 1993 as a consequence of the growing concern regarding the escalation of violence in Colombia; its objective is to create an econometric model capable of forecasting the path of terrorist murder under different policy options and helping the country in the design of state policy drawing the lineaments for reaching the pacification of the country. I claim that the approach presented here is the only way of creating an econometric model for terrorist murder in Colombia. In the first part I use The Beveridge and Nelson decomposition of economic time series to estimate the cyclical component of murder, which is used later to construct a theoretically and statistically satisfying model to account for cyclically motivated terrorist murder in Colombia, 1950-2004. The variables that together account for eighty three percent of the variation in cyclical terrorist murder are the years of Colombia’s La Violencia period when the peasant self-defense movements appeared, the years of the so-called National Front political collusion between the two main establishment parties, the real trade balance, the size of Colombia’s military forces as a proxy for all armed forces (military, para-military, guerrilla, and drug-related) in the country, the unemployment rate, the number of students matriculated in all modalities and people displaced in the country. The forecasts for cyclical terrorist murder for 2003-2004 show the big dilemma facing the Colombian authorities: the strong reduction of displaced people from 212,000 in 2003 to 117,000 in 2004 boosted the cyclical terrorist murder in the countryside, erasing the initial results by president Uribe’s administration at controlling the intensity of the conflict and implying that any future policy at diminishing it should control the number of displaced people, one of the biggest problems facing Colombia today. The final section presents forecasts for 2005-2019 suggesting, that peace will be attained around year 2008 and, that the way, at this point to reach sustainable peace is through the continuation of the Democratic Security Policy and strong presidential leadership headed towards disarmament of all armed actors in the country combined with the implementing of political and social changes that will secure lasting peace before year 2019.Colombia; Beveridge and Nelson; cyclical terrorist murder; democratic security policy; sustainable peace; permanent peace; lasting peace